The future of HR : understanding knowledge management for motivation, negotiation, and influence - Sætersdal, Helene; Johannessen, Jon-Arild (Emerald Publishing Limited, 2019)
HR departments are in transition. From 1980 to today, HR management has shifted into a strategic function of the company. The globalisation, digitalisation and techno-focus of the modern workplace is at the centre of a new organizational design, and with change comes resistance, particularly for employees who see this new design as a threat to their positions. For people to keep up with technology, HR management must evolve to embrace these changes.Through a student-led perspective, leadership experts Jon-Arild Johannessen and Helene Sætersdal discuss how the HR department can develop to face the challenges of the 21st Century, including new roles and functions to create an ambidextrous organisation. With 51 reflection tasks throughout, Johannessen and Sætersdal help students explore how to reduce resistance to organisational change and create a healthy work environment, through techniques such as mindfulness, negotiation, and enthusiasm. This is an ideal read for any student of management and leadership looking to understand the challenges HR departments are facing, and how they can help change the way the game is played for the future of work.